2021
DOI: 10.1101/2021.05.24.445471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple Causal Variants Underlie Genetic Associations in Humans

Abstract: The majority of associations between genetic variation and human traits and diseases are non-coding and in strong linkage disequilibrium (LD) with surrounding genetic variation. In these cases, a single causal variant is often assumed to underlie the association, however no systematic assessment of the number of causal variants has been performed. In this study, we applied a massively parallel reporter assay (MPRA) in lymphoblastoid cells to functionally evaluate 49,256 allelic pairs, representing 30,893 gene… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 72 publications
3
29
0
Order By: Relevance
“…The remarkable complexity in causal variants we uncovered underscores the challenge of predicting variant effects on UPS protein degradation. Similar to recent results 47, 85 , each of the four QTL regions we fine-mapped contained multiple causal variants in a single gene (Figures 3/4). In the case of NTA1 , we observed that the effect of the D111E variant was likely masked during QTL mapping by the larger effect of the E129G variant (Figure 4C), highlighting the need to test individual variants in isolation.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The remarkable complexity in causal variants we uncovered underscores the challenge of predicting variant effects on UPS protein degradation. Similar to recent results 47, 85 , each of the four QTL regions we fine-mapped contained multiple causal variants in a single gene (Figures 3/4). In the case of NTA1 , we observed that the effect of the D111E variant was likely masked during QTL mapping by the larger effect of the E129G variant (Figure 4C), highlighting the need to test individual variants in isolation.…”
Section: Discussionsupporting
confidence: 85%
“…Previous efforts to understand how genetic variation influences gene expression have revealed considerable discrepancies between genetic effects on mRNA versus protein abundance [40][41][42][43][44][45][46][47][48] . Many gene expression QTLs alter protein abundance without detectable effects on mRNA levels.…”
Section: Protein-specific Effects Of Ubr1 -469a>t On Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis shows that several credible set variants overlap either with transcription start sites or enhancer regions, providing additional support for potential causal variants. Considering recent studies, it is plausible that there are several tightly linked causal variants in each locus 55 and functional studies are needed for further fine-mapping.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] However, linkage disequilibrium (LD) within each locus along with the presence of multiple causal alleles within or between cell types may skew the quantification of sharing of genetic effects between tissues and impede our ability to identify causal variants. Indeed, recent research has demonstrated that multiple causal variants are often present in many eQTL and complex-trait-associated loci, 9,10 suggesting that allelic heterogeneity may be more com-mon than previously anticipated and underscoring the importance of disentangling causal signals in high-LD regions. These complex patterns could hinder the identification of regulatory effects for disease-associated genetic variants, potentially obscuring both the relevant cell type and target gene.…”
Section: Introductionmentioning
confidence: 99%